Colônia Cecília – An Anarchist Adventure in America and Education: A study on Education in the literary representation of Colônia Cecília in the work of Afonso Schmidt (Research, Society and Development, 2023)
The research object of this article is the literary work Colônia Cecília: Uma Aventura Anarquista na América, written in 1942 by Afonso Schmidt. The work was analyzed from bibliographical references on the use of literature as a historical source. The objective of this work was to examine the references contained in Schmidt's work on education, comparing these references with the author's contemporary educational models, mainly the educational concepts linked to different anarchist currents between the end of the 19th century and the beginning of the 20th century, taking into account care when using literature as a historical source. Schmidt's educational concepts and political inclinations were discussed, as well as his imaginary about education in the period of the establishment of Colonia Cecília in Brazil.